Multicultural-Based Islamic Religious Education Development Model in The Samudra University Contexts, Aceh Province - Azmi, Muhammad Faisal; Moeljadi, Moeljadi; Chanifah, Nur; Mahfur, Muhammad; Diani, Khonita Rahma (Wacana Journal of Social and Humanity Studies, 2025)
Education is one of the most effective forms of media to give birth to a generation with views that can make diversity a part of unifying the nation. Islamic religious education has actually contained the discourse of multiculturalism, but at the level of implementation, it has not been implemented properly. Efforts are needed to redesign the Islamic religious education system based on multiculturalism so that Islamic religious education is more optimal in disseminating multicultural discourse to students. This research aims to formulate the model's implications for developing multicultural-based Islamic religious education at Samudra University, Langsa City, Aceh Province. The type of research used in this research is R&D/Research and Development. Data collection in this study was carried out through observations, interviews, and document searches. The results of the interviews showed that the methods used in learning at Unsam were lectures and discussions, and sources of material could be books, the internet, previous research, and relevant journals.  So far, Unsam students have good multicultural traits such as tolerance, cooperation, and not being picky in making friends, and these traits are reflected in their daily lives. The material in the RPS shows several materials related to multiculturalism, namely inter-religious harmony, Islamic democracy, civil society, and the welfare of the people, as well as Islam building unity and diversity. To increase the effectiveness of learning, the method that can be given is the brain-based learning method combined with lectures, discussions, or case studies. Another improvement that can be given is to improve the form of learning evaluation and provide training to lecturers to equalize perceptions related to multiculturalism. Materials on multiculturalism can be added with materials on preventing radicalism in students. Keywords: curriculum, education, multicultural, university